Development Of Interactive Multimedia For Learning Computer Hardware Maintenance Vocational High School - Hermanus Herawan; Aloysius Mering; Herry Sujaini (JETL (Journal of Education, Teaching and Learning), 2022)
The aim of this reasearch was to develop interactive multimedia for learning computer hardware maintenance in Vocational High Schools. To achieve the objectives of this study, the Research and Development (R&D) method of the ADDIE development model was used. The ADDIE development model in research begins through the stages (1) Analyze, (2) Design, (3) Develop, (4) Implement, and (5) Evaluate. This research was conducted Vocational High School Negeri 6 Pontianak at class X with 27 students participating and three validators, design experts, material experts, and media experts. Data from the instrument and attitude scale were analyzed using qualitative and quantitative analysis. Relatively, from the results of data analysis (in the range of values 1-5) the multimedia design was declared "very valid" with an average of 4.34. Followed by analysis of empirical test data with individual test procedures, small groups, and field tests on 27 students of Vocational High School Negeri 6 Pontianak in class X, showing the attitude of students "very happy" using interactive multimedia with an average of 6.26 in the range 1-7. The multimedia effectiveness test with the criteria of students' attitudes towards multimedia and the pretest and posttest scores involving 30 students turned out to be a significant difference with ???????? ≥ ????????????????????????,, namely 13,507  ≥  2,045. Based on the results of research, interactive multimedia for learning computer hardware maintenance at Vocational High Schools can be applied to basic computer network subjects